ROLE OF COMMAND AREA DEVELOPMENT PROGRAMME IN DEFUSING THE PROBLEMS OF WATERLOGGING AND SALINISATION IN THE IRRIGATION PROJECTS. - Dinkar, V.S. (Journal of Soil and Water Conservation, 2022)
The Command Area Development Programme, a Centrally Sponsored Scheme, was launched in the beginning of the Fifth Five Year Plan ( 1974 -75) to optimise the irrigation efficiency in Major Medium Irrigation Projects. I aimed at raising the Agricultural Production to the optimal level in the irrigation commands on sustainable basis. This paper describes as to how the Command Area Development Programme conceived to optimise the canal irrigation water use efficiency and thus defusing the twin problems of waterlogging and salinisation, and hehow far it has succeeded in its objective, what are the constraints and what could be done for the possible remedies.